Intramammary inoculation of Panax ginseng plays an immunoprotective role in Staphylococcus aureus infection in a murine model - Silvestrini, Paula; Beccaria, Camila; Pereyra, Elizabet Amanda Lorena; Renna, María Sol; Ortega, Hugo Hector; Calvinho, Luis Fernando; Dallard, Bibiana Elisabet; Baravalle, Celina (2018)
The immunoprotective effect of Panax ginseng (Pg) extract was investigated in a mouse mastitis model. Lactating female mice were intramammarily inoculated with Pg or placebo, and then were challenged with S. aureus, while other group was inoculated with S. aureus alone. The number of bacteria recovered from mammary glands was significantly lower in Pg-treated S. aureus-infected mice (group I) compared with placebo-treated S. aureus-infected mice (group II) and S. aureus-infected mice (group III). The mRNA expression of TLR2, TLR4, IL-1α and TNF-α was influenced by treatment; being the transcript levels for all genes higher in group I compared with group II and III. Activation of NF-κB and the number of monocytes-macrophages in mammary gland tissue was significantly increased in group I compared with group II and III. Pg extract was able to trigger an adequate immune response to confront an infection demonstrating its protective effect and potential for preventing bovine intramammary infections.